E-Commerce and Web Technologies 15th International Conference, EC-Web 2014, Munich, Germany, September 1-4, 2014, Proceedings - Hepp, Martin; Hoffner, Yigal (Lecture Notes in Business Information Processing, 2014)
This book constitutes the refereed proceedings of the 15th International Conference on Electronic Commerce and Web Technologies (EC-Web) held in Munich, Germany, in September 2014. The 11 full and 8 short papers included in this volume were carefully reviewed and selected from 46 submissions. The papers are organized in topical sections on data, information, and knowledge management for e-business; Semantic Web and linked open data for e-business; search, matchmaking, recommender and comparison systems; economics, management, and law; and social interaction in e-business.